2010
DOI: 10.1021/ef1012038
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Particle Dynamics (DPD) Study of Crude Oil−Water Emulsions in the Presence of a Functionalized Co-polymer

Abstract: This work presents a theoretical study of the effects of different molecular weights of a triblock co-polymer ethylene oxide/propylene oxide/ethylene oxide, bifunctionalized with ethalamine, on the coalescence of water drops imbibed in a crude oil environment. The polymer/crude oil/water (PCW) time evolution of the emulsion was simulated using the framework of the dissipative particle dynamics (DPD) technique. The bead-bead interactions of the molecular components were calculated using the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 50 publications
1
73
0
Order By: Relevance
“…Where a ij is a maximum repulsion between particle i and particle j , r ij = r j − r i,, r ij = | r ij | and r ˆ ij = r ij /| r ij | 23 45 50 51 . The inter-particle force is repulsive over a limited range only and acts in the direction of the r ij vector.…”
Section: Methodsmentioning
confidence: 99%
“…Where a ij is a maximum repulsion between particle i and particle j , r ij = r j − r i,, r ij = | r ij | and r ˆ ij = r ij /| r ij | 23 45 50 51 . The inter-particle force is repulsive over a limited range only and acts in the direction of the r ij vector.…”
Section: Methodsmentioning
confidence: 99%
“…For example, demulsification of heavy crude oil emulsions in the presence of a functionalized copolymer was investigated by Alvarez et al by using the framework of the DPD simulation. 37 It was found that the copolymer with short-chains was more effective to accelerate the water coalescence than that of with long chains. In this work, an all-atom model was employed by using MD simulation to study the aggregation of asphaltene molecules at the water/ oil interface.…”
Section: Introductionmentioning
confidence: 99%
“…13,22 DPD simulations method are an excellent technology for the simulation of coarse-grained systems over considerable length and time scales up to the mesoscopic scale. 13,20 DPD simulations have been performed to study static and dynamic interfacial phenomena and the self-assembly behavior of amphiphilic molecule at the interface, 20,21 including asphaltenes at liquid/ liquid interface 22 and the solid/liquid interface. 23 In this study, we have used three types of asphaltene molecules with different molecular weights, which was constructed from a statistical representation of the oil sample.…”
Section: Introductionmentioning
confidence: 99%